2020
DOI: 10.22219/jiz.v3i1.11682
|View full text |Cite
|
Sign up to set email alerts
|

Learning of Imla’ Using Flashcards on Writing Skill at Islamic Elementary School Level in Samarinda

Abstract: There are some language skills, one of them is writing which has the steps of learning a foreign language. Writing skill has the most difficult skill. The use of instructional media has functions to facilitate teaching and learning activities, especially in Arabic learning of Imla’ material. The flashcard is used as a medium to facilitate teaching and learning activities of Imla’ for non-Arabic students. This research aimed to describe learning of Imla’ on Arabic writing skill and describe learning implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Additionally, the results align with Ngarofah and Sumarni (2019), who reported improving students' vocabulary mastery after using flashcards. Furthermore, the effectiveness of flashcards in vocabulary learning has been supported by various studies (Pimada et al, 2020;Azabdaftari & Mozaheb, 2012;and Alghamdi & Elyas, 2020), all of which highlighted the positive impact of flashcards on vocabulary acquisition. Moreover, the results are consistent with the findings of Apfani et al (2022), which showed a significant improvement in student vocabulary scores after using flashcards.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, the results align with Ngarofah and Sumarni (2019), who reported improving students' vocabulary mastery after using flashcards. Furthermore, the effectiveness of flashcards in vocabulary learning has been supported by various studies (Pimada et al, 2020;Azabdaftari & Mozaheb, 2012;and Alghamdi & Elyas, 2020), all of which highlighted the positive impact of flashcards on vocabulary acquisition. Moreover, the results are consistent with the findings of Apfani et al (2022), which showed a significant improvement in student vocabulary scores after using flashcards.…”
Section: Discussionmentioning
confidence: 87%
“…Unmotivated students can hardly learn anything, especially when that "thing" is an essential and demanding skill in the calibre of writing. As students are at present largely comprised of the so-called "millennials" and "Generation Z" (or Zoomers), enhanced automation infrastructure can be introduced to improve students' overall digital learning using the tools they are used to and are welcomed by them (Al-Ahdal, et al, 2014;Alfallaj and Al-Ahdal, 2017;Pimada, et al, 2020;Valizadeh and Soltanpour, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This card media is media that is suitable for the state of students who are weak in hearing. As revealed by Pimada, Toba and Rasyidi (2020) that the use of card media can…”
Section: The Implementation Of Learning Arabic Alphabets For Special Needs Students In Elementary School At Campurdarat Tulungagung East mentioning
confidence: 99%